2016
DOI: 10.1044/2016_jslhr-h-15-0170
|View full text |Cite
|
Sign up to set email alerts
|

Task- and Talker-Specific Gains in Auditory Training

Abstract: The findings support applications of transfer-appropriate processing to auditory training and favor tailoring programs toward the specific needs of the individuals being trained for tasks, talkers, and perhaps, for stimuli, in addition to other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Based on their recent meta-analysis, Henshaw and Ferguson (2013) suggested that the efficacy of computerized auditory training for adults is "not robust" and that there was a paucity of evidence-based studies to assess efficacy (see also Sweetow & Palmer, 2005). The present findings add to the growing amount of evidence that training can be effective and robust (e.g., Barcroft et al, 2011bBarcroft et al, , 2016Burk, Humes, Amos, & Strauser, 2006;Sweetow & Henderson-Sabes, 2006;Tye-Murray et al, 2016).…”
Section: Activity Groupsupporting
confidence: 70%
See 3 more Smart Citations
“…Based on their recent meta-analysis, Henshaw and Ferguson (2013) suggested that the efficacy of computerized auditory training for adults is "not robust" and that there was a paucity of evidence-based studies to assess efficacy (see also Sweetow & Palmer, 2005). The present findings add to the growing amount of evidence that training can be effective and robust (e.g., Barcroft et al, 2011bBarcroft et al, , 2016Burk, Humes, Amos, & Strauser, 2006;Sweetow & Henderson-Sabes, 2006;Tye-Murray et al, 2016).…”
Section: Activity Groupsupporting
confidence: 70%
“…However, in light of previous findings in this area, training on the task is desirable, and hearing health care specialists should train patients to recognize the very speech stimuli and the very talkers that any given person with hearing loss desires. This approach is precisely like that taken in several recent studies (Barcroft et al, 2011b(Barcroft et al, , 2016, wherein we trained persons with hearing loss to discriminate the speech of their significant others (Tye-Murray et al, 2016) and achieved gains in a four-choice discrimination task of approximately 14% words correct. At issue here is how generalizability actually reflects the degree to which the component perceptual and cognitive processes engaged during training overlap with those that underlie the desired outcome when it comes to task, stimulus, and talker (see Barcroft et al, 2016).…”
Section: Activity Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…9) have been developed and marketed in the US for ICTbased aural training [23,24]. However, they focus on enhancing the aural memory mainly using ambient sounds, not speech and do not support Korean, which are limitations [23,24]. Therefore, it is necessary to develop a cochlear implant hearing rehabilitation training program suitable for native Korean speakers.…”
Section: Development Status and Trend Of Online Aural Rehabilitmentioning
confidence: 99%